2023
DOI: 10.1002/fsn3.3486
|View full text |Cite
|
Sign up to set email alerts
|

An investigation on the prevalence of microplastic in commercial and open pan salts obtained from Cox's Bazar and Maheshkhali region of Bay of Bengal (Bangladesh)

Abstract: Unrestrained utilization of plastic has reached an intemperate state, menacing environment and human lives. The preliminary focus of this research was to investigate and divulge the contemporary status of microplastics (MPs) in commercialized and open pan salts from Cox's Bazar and Maheshkhali channels. A total of 27 samples were obtained. The samples were analyzed for the prevalence of MPs by FTIR and Raman spectroscopy (RS); the prevailing amount, color, size, and shapes were analyzed by stereomicroscope and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 72 publications
0
1
0
Order By: Relevance
“…On other hand, Nithin et al [ 58 ] documented exclusively fibers in their samples. Mazumder et al [ 69 ] reported a higher prevalence of fibers (79 %) compared to fragmented particles (19.9 %). Additionally, Makhdoumi et al [ 24 ] observed a majority of fragments (78.57 %) with a smaller proportion of fiber-shaped microplastics (21.43 %).…”
Section: Resultsmentioning
confidence: 99%
“…On other hand, Nithin et al [ 58 ] documented exclusively fibers in their samples. Mazumder et al [ 69 ] reported a higher prevalence of fibers (79 %) compared to fragmented particles (19.9 %). Additionally, Makhdoumi et al [ 24 ] observed a majority of fragments (78.57 %) with a smaller proportion of fiber-shaped microplastics (21.43 %).…”
Section: Resultsmentioning
confidence: 99%